Risk/investment-driven transmission expansion planning with multiple scenarios - Rahmani, Mohsen [UNESP]; Romero, Ruben A. [UNESP]; Rider, Marcos J. [UNESP] (Institution of Engineering and Technology (IET), 2013)
This study presents a new methodology based on risk/investment to solve transmission network expansion planning (TNEP) problem with multiple future scenarios. Three mathematical models related to TNEP problems considering multiple future generation and load scenarios are also presented. These models will provide planners with a meaningful risk assessment that enable them to determine the necessary funding for transmission lines at a permissible risk level. The results using test and real systems show that the proposed method presents better solutions compared with scenario analysis method. ©The Institution of Engineering and Technology 2013.
Keywords: Future generations; Real systems; Risk levels; Scenario analysis; Transmission expansion planning; Transmission network expansion planning; Mathematical models; Risk assessment